India's System of Intergovernmental Fiscal Relations - Nirvikar Singh (University of California, Economics Department, 2004)
This paper examines several aspects of India's system of Intergovernmental Fiscal Relations (IGFR). It first reviews the origins and context within which the IGFR system was established and examines how it has evolved. It describes the nature of the system, including assignment of powers and functions, intergovernmental fiscal transfers and the principles that guide their design. It examines several other dimensions of the IGFR system, such as its interface with policy imperatives, evolution of norms, and recent institutional developments. It concludes with an assessment of lessons learned so far, and key challenges that lie ahead.
Keywords: 330